Work Motivation Effect on State Civil Apparatus Performance during WFH with Discipline Variable - Bawono, Icuk Rangga; Setyadi, Erwin; Hamid, Suhaila Abdul (AKRUAL: JURNAL AKUNTANSI, 2020)
Civil apparatus of the state should remain optimal in providing service to the community at the time of running work from home as a pandemic impact of Covid-19. Bureaucratic performance should also be maintained to ensure government programs can be directly perceived by the public. Governments are required to be able to apply flexible work patterns from two sides. That is flexible from the side of the work implementation, and flexible from the user side that in this case is the community.Â  Despite working from home, the state civil apparatus is required to be able to provide optimal performance. This research seeks to see the motivation influence of state civil apparatus on their performance either directly or through disciplinary variables. Quantitative design has been adopted for this study using survey questionnaires prepared based on the Likert Scale (strongly disagree -1 and 5 to strongly agree). The sample size consists of 100 state civil apparatuses and is processed using PLS. The results of this study concluded that direct motivation does not affect performance, but indirectly through discipline, motivation can influence a significant effect at the overall performance of civil apparatus of the state